Assessment of a liquid hydrogen conditioning system for retrofitting on kerosene designed turbofans - Rompokos, Pavlos; Kyritsis, Vasileios; Mourouzidis, Christos; Roumeliotis, Ioannis (American Society of Mechanical Engineers (ASME), 2025)
As energy transition to alternative fuels for civil aviation is likely to be gradual, hydrogen’s first entry to service may be implemented on existing gas turbine engines. In this paper a novel liquid hydrogen conditioning system for retrofitting on kerosene designed geared turbofans is assessed in terms of performance and engine rematching. The aim of the analysis is to identify emerging requirements for the design of the fuel and thermal management system within the constraints of a certified engine design. The conditioning system proposed, an LH2 preheater, enables the control of the gaseous hydrogen temperature at combustor entry and consists of a secondary combustor and a heat exchanger. The examined configuration considers various bleed source locations within the engine to supply the preheater system. For performing the analysis, a kerosene fueled engine has been designed and suitable integrated models capable to simulate the retrofitted hydrogen fueled engine as well as the LH2 preheater operation have been developed. The system performance has been analyzed for the different bleed source locations identifying operating limits and performance changes. From all the examined bleed source positions, utilizing the by-pass duct minimizes the impact on component rematching and engine efficiency. Additionally, through a gas path geometry multiparametric analysis, it was found that by readjusting the capacity of the high-pressure turbine and the core nozzle area the certified limits can be met for the retrofitted engine.
Keywords: 40 Engineering; 4001 Aerospace Engineering; 7 Affordable and Clean Energy; Energy; 4004 Chemical engineering